2003
DOI: 10.1002/eat.10129
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and differential access to care for eating disorder symptoms

Abstract: These data suggest that clinician bias may be an important barrier to access to care for eating disorder symptoms in ethnic minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
189
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(195 citation statements)
references
References 15 publications
(10 reference statements)
5
189
0
1
Order By: Relevance
“…44 Moreover, a recent study indicated that physicians were significantly less likely to inquire about eating disorder symptoms among ethnic minorities than among nonminority patients. 45 The Arabs in Israel are raised with a fundamental conflict between two very different systems of values and perspectives: Western/modern and traditional. 46 The current results may reflect such a conflicting value system.…”
Section: Resultsmentioning
confidence: 99%
“…44 Moreover, a recent study indicated that physicians were significantly less likely to inquire about eating disorder symptoms among ethnic minorities than among nonminority patients. 45 The Arabs in Israel are raised with a fundamental conflict between two very different systems of values and perspectives: Western/modern and traditional. 46 The current results may reflect such a conflicting value system.…”
Section: Resultsmentioning
confidence: 99%
“…This single study examined case records from a consecutive series of Indigenous Alaskan patients presenting at a community mental health center. 9 However, given the well documented barriers to seeking care and biases in clinicians' diagnostic assessments, [10][11][12] a clinicbased sample is highly likely to underestimate true prevalence. Only two other studies report data concerning prevalence of symptoms of eating disorders in AI/NA adults, but have limited application to true prevalence estimates in AI/NA communities.…”
Section: Introductionmentioning
confidence: 99%
“…Only two other studies report data concerning prevalence of symptoms of eating disorders in AI/NA adults, but have limited application to true prevalence estimates in AI/NA communities. For example, one study identified symptoms via the National Eating Disorders Screening Program conducted on US college campuses in 1996 (reported in two separate publications 10,13 ). Data collected during this screening program did not estimate prevalence of specific eating disorders, although it did ask respondents about a previous diagnosis or care for an eating disorder.…”
Section: Introductionmentioning
confidence: 99%
“…9 Ethnic differences in help-seeking behavior and in physicians' evaluations and referrals for treatment have been reported. 10 Even after controlling for severity of self-reported eating disorder symptoms, Becker and colleagues found that minority women were less likely to seek eating disorder treatment. Further, they found that physicians were less likely to inquire about eating disorder symptoms in minority patients and less likely to refer them for further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they found that physicians were less likely to inquire about eating disorder symptoms in minority patients and less likely to refer them for further evaluation. 10 Cachelin et al, 11,12 found that ethnic minorities were less likely to seek help for an eating disorder, despite an expressed desire for treatment. The most commonly cited reason was financial constraints.…”
Section: Introductionmentioning
confidence: 99%